Assessment of vitamin d status among egyptian covid-19 patients - Marwa Ahmed Salah Ahmed; Mohamed Nabil Soliman Atta; Mona Abdel-Latif; Mona Moustafa Tahoun; Sarah Abd El Rahim Rady Abd Allah (SpringerOpen, 2024)
Abstract Background The COVID-19 outbreak has increased awareness of vitamin D's (Vit-D) potential advantages for both prevention and treatment. Adequate vitamin D levels are necessary for health of the immune system, which can help with cellular response and protection against the severity of microbial infection. Purpose To evaluate Vit-D levels and their association with illness severity in Egyptian COVID-19-infected individuals. Methods This case-control investigation was performed at the Alexandria Main University Hospital on 80 subjects divided into 2 groups: 40 COVID-19 patients and 40 healthy persons to measure the Vit-D levels of the Egyptian cohort. Results There was a statistically insignificant difference in the Vit-D serum levels of the studied groups (P = 1.000). The age of the Vit-D insufficient patients was significantly higher than that of Vit-D sufficient patients (P = 0.006). There was a statistically insignificant rise in the CRP level in the Vit-D insufficient patients (P = 0.862) compared to patients with sufficient Vit-D. Also, the D-dimer levels in Vit-D-insufficient patients were considerably higher (P = 0.015). Patients with sufficient Vit-D exhibited significantly lower levels of IL-6 than Vit-D insufficient patients. (P = 0.037). Patients in the Vit-D-insufficient subgroup needed substantially more breathing support than those in the Vit-D-sufficient group (P = 0.020). Conclusion Although there was no association between both levels of Vit-D and the COVID-19 infection risk, insufficiency of Vit-D was related to more severe infection.